RESEÑA : Barrero Ortega, Abraham. La libertad religiosa en España. Madrid : Centro de Estudios Políticos y Constitucionales, 2006 - Vázquez Alonso, Víctor Javier (Teoría y Realidad Constitucional, 2007)
The work by professor Abraham Barrero deals exhaustively with the regulation of religious freedom in the Spanish legal system. In the first part of his book, he performs a historical review of r eligious fr eedom in the Spanish constitutionalism. Next, he proceeds to analyze the constitutional profiles of freedom in the Constitution of 1978. Finally, he examines the normative developments of religious freedom in light of the constitutional principles. The author underlines the relevance of the individual dimension of r eligious freedom, and highlights the relationship between this right and equity, and with the principle of state-church separation. Because of its comprehensiveness and consistency it may well be considered the most relevant doctrinal contribution on this subject in the last years.